Association of hyperuricemia and serum uric acid lowering therapy with mortality in hemodialysis patients. Issue 1 (1st January 2020) - Rohn, Benjamin; Jansing, Wiebke; Seibert, Felix S.; Pfab, Thiemo; Cinkilic, Okan; Paßfall, Jürgen; Schmidt, Sven; Babel, Nina; Bauer, Frederic; Westhoff, Timm H.
Abstract: Introduction: In the general population, hyperuricemia is associated with increased morbidity and mortality. Data on this association in hemodialysis patients is controversial. Moreover, it remains elusive whether serum uric acid (SUA) lowering therapy is associated with mortality. Methods: Retrospective analysis of 601 patients on chronic hemodialysis therapy in five outpatient centers with a maximum follow-up of 100 and a mean follow-up of 41 months. Death was defined as primary endpoint. Cumulative survival was analyzed by Kaplan–Meier analysis and Cox regressions adjusted for age. Findings: Cumulative survival rates were higher for those subjects with a higher than median SUA concentration both based on mean annual and baseline measurements ( p < 0.05 each). There was no survival difference anymore after adjustment for age ( p > 0.05 each). Stratification for SUA lowering therapy (allopurinol/febuxostat) had no impact on cumulative survival, neither in Kaplan Meier nor in Cox regression analyses ( p > 0.05 each). Furthermore, Cox regression analysis excluded an increased cardiovascular mortality in subjects with hyperuricemia. Discussion: In contrast to the general population, hyperuricemia is not associated with increased mortality in patients undergoing hemodialysis. Moreover, xanthine oxidase inhibition was not associated with a survival benefit in this analysis. These data do not support the use of SUA lowering medication in hemodialysis patients with asymptomatic hyperuricemia.